2020
DOI: 10.1080/13102818.2020.1736952
|View full text |Cite
|
Sign up to set email alerts
|

Determination of residual monomer content in dental acrylic polymers and effect after tissues implantation

Abstract: The aim of the present study was to determine the content of residual monomer methyl methacrylate (MMA) in cold and hot polymerized poly(methyl methacrylate) (PMMA), both widely applicable in dentistry, by using MHE-GC-MS (multiple headspace extraction analysis by gas chromatographymass spectrometry) in combination with GC-FID (gas chromatography with flame-ionization detection). The samples of PMMA were obtained by free-radical polymerization of MMA at room temperature (cold polymerized PMMA) and at 100 C (ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…[9][10][11] These species, such as methyl methacrylate (MMA), dimethacrylate (crosslinking) parent monomers, catalysts or formaldehyde are released after short intraoral exposure periods, 12,13 whereas hydrolytic or biodegradation byproducts are released after long intraoral exposure. 10,11,[14][15][16] Since MMA is the main eluent from heat-cured PMMA denture base resins, many laboratory methods have been developed to quantify residual MMA monomer in the polymerized materials, such as infrared spectroscopy, 17 gas chromatography (GC), [18][19][20] high-performance liquid chromatography (HPLC) [21][22][23][24][25][26] and ultraviolet spectrophotometry. 27,28 From these methods, the chromatographic analyses offer higher detection and quantification limits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] These species, such as methyl methacrylate (MMA), dimethacrylate (crosslinking) parent monomers, catalysts or formaldehyde are released after short intraoral exposure periods, 12,13 whereas hydrolytic or biodegradation byproducts are released after long intraoral exposure. 10,11,[14][15][16] Since MMA is the main eluent from heat-cured PMMA denture base resins, many laboratory methods have been developed to quantify residual MMA monomer in the polymerized materials, such as infrared spectroscopy, 17 gas chromatography (GC), [18][19][20] high-performance liquid chromatography (HPLC) [21][22][23][24][25][26] and ultraviolet spectrophotometry. 27,28 From these methods, the chromatographic analyses offer higher detection and quantification limits.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that an increased MMA/PMMA ratio leads to an increased amount of residual MMA in the set material, 10 with heat-cured materials possessing less residual monomer than the self-cured. 16,21 Furthermore, studies show that many procedures can reduce the MMA concentration, such as choosing a curing temperature of 100°C, 5,11,29 extending the polymerization time, [29][30][31] implementing a post-polymerization regime at 55°C for 60 min by exposure to microwave irradiation 24 or by smearing acrylic resin with a light-cured coating. 32 Recently, it has been documented that the cooling procedures of the processing flasks affect some mechanical properties of heat-cured denture base PMMA materials, 33 which may be assigned to post-curing reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The residual monomer content present in cold polymerised PMMA was higher than that of heat polymerised PMMA, with cold polymerised material also showing a greater inflammatory response of soft tissue. Tuna et al [4] noted that as the primary difference between heatand self-cured materials is the liquid-to-powder ratio, and taking the study by Kostić et al [22] into account, it can be confirmed that the amount of unreacted monomer present in the material after polymerisation directly affects the degree of solubility expressed by the material. These observations may not only be as a result of different liquid-to-powder ratios, as both Tuna et al [4] and Kostić et al [22] compared the heat-cure acrylic to self-cure acrylic.…”
Section: Mixing Ratiosmentioning
confidence: 98%
“…Tuna et al [4] noted that as the primary difference between heatand self-cured materials is the liquid-to-powder ratio, and taking the study by Kostić et al [22] into account, it can be confirmed that the amount of unreacted monomer present in the material after polymerisation directly affects the degree of solubility expressed by the material. These observations may not only be as a result of different liquid-to-powder ratios, as both Tuna et al [4] and Kostić et al [22] compared the heat-cure acrylic to self-cure acrylic. Heat-cure and self-cure acrylics do not only have different liquid-to-powder ratios, but different activators and polymerisation procedures as well.…”
Section: Mixing Ratiosmentioning
confidence: 98%
See 1 more Smart Citation